ANALISIS TEKS PEMILIHAN UMUM PADA PORTAL MEDIA AL-AHRAM - Luthfi Wildan Jamil (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study discusses the general elections that took place in Syria, where one of the candidates was a woman, which is a new thing for Arab countries. This study method uses a qualitative approach and descriptive method, the research data is analyzed and identified narratively. The purpose of this study is to show the intrinsic and extrinsic elements in the news of the general election. The results of this study show that the presentation of general election news in Al-Ahram media includes intrinsic and extrinsic elements, but there is one thing that is not fulfilled in extrinsic elements, namely conflict.